Methodology to favour the teaching learning of the technique of kick mondolyo dwit furio chagui in the taekwondistas of the category 9-10 years (Original) (Revista científica Olimpia, 2020)
The investigation responds to the technological demand of the Tae Kwon Do in the Granma  Province, seeking with our modest effort to contribute the sport development of students and  trainers, we approach inside the sport preparation the process of teaching learning of the  techniques of kick of the Tae Kwon Do in the sport initiation. To give solution in the process of  technical preparation to the correct teaching learning of the technical Mondollyo Dwit Furio  Chagui, with a scientific focus of great importance, for the changes that it demands the current  sport preparation. This investigation was developed in the Sport Cocktail Camilo Cienfuegos of  the Municipality Bayamo with students of the category 9-10 years of the masculine sex; of a  registration of 16, he/she took a sample eight athletes that represent 50% of the registration that  present difficulty in the execution of the technique of I kick Mondollyo Dwit Furio Chagui and they  lack specialized sport experience. For the development of the investigation we use the such  empiric methods as; the observation, the mensuration, the experiment, the interview technique  and the documental revision, and the theoretical methods as the historical one logical, inductive  deductive, the analysis synthesis and systemic structural, as well as the mathematical  percentage calculation.
Keywords: taekwondo; technique; preparation; methodology